The impact of modifying 3D printing parameters on mechanical strength and physical properties in vat photopolymerisation - Alice M G Cheadle; Eva Maier; William M Palin; Phillip L Tomson; Gowsihan Poologasundarampillai; Mohammed A Hadis (Scientific Reports)
Abstract Vat photopolymerisation is frequently used to produce parts through additive manufacture by way of layer-by-layer resin polymerisation. A post curing process is often used to ensure optimised polymerisation of the printed structures. The part to be printed is digitally orientated in relation to the principal building axis and build platform. The effects of part (or object) print orientation, post-cure time / temperature on mechanical and physical properties were investigated. Scaled ASTM D638 dumbbell shaped specimens were printed to measure mechanical properties and degree of conversion; printed cylindrical discs (15 mm diameter, 1.6 mm thick) were printed to evaluate colour change and UV-absorbance. Dumbbell shaped specimens with principal axis perpendicular to the build platform had significantly better tensile strength (p < 0.05) and degree of conversion (p < 0.05). Increased post-cure temperature and time significantly influenced degree of conversion, yellowing of samples and tensile strength (p < 0.05). This study highlights the importance of optimising both orientation of build and post-cure parameters, as well as potential to exploit post-cure protocols to overcome anisotropy, which is of great clinical importance in applications such as dental restorations, bone scaffolds and prostheses. Knowledge of how to optimise physical and mechanical properties of SLA-printed parts in the context of the application is essential for anyone directly or indirectly employing the technology.